2018
DOI: 10.7566/jpsj.87.124004
|View full text |Cite
|
Sign up to set email alerts
|

Variational Wave Function for Inhomogeneous Bose–Einstein Condensate with 3/2-Body Correlations

Abstract: We construct a variational wave function for inhomogeneous weakly interacting Bose-Einstein condensates beyond the mean-field approximation by incorporating 3/2-body correlations. From our numerical results calculated for a system trapped by a one-dimensional harmonic oscillator, the 3/2-body correlations give a contribution comparable to the meanfield energy toward lowering the ground-state energy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…That is, it is considered that our formalism is a natural extension of the zero-temperature formalism. [17][18][19] On the other hand, we note that Eq. (A·14) cannot be used to solve the self-consistent equations because A (1) k (ε) expressed by Eq.…”
Section: (A·15)mentioning
confidence: 91%
See 3 more Smart Citations
“…That is, it is considered that our formalism is a natural extension of the zero-temperature formalism. [17][18][19] On the other hand, we note that Eq. (A·14) cannot be used to solve the self-consistent equations because A (1) k (ε) expressed by Eq.…”
Section: (A·15)mentioning
confidence: 91%
“…15,16) In recent years, however, we constructed a variational wave function for the ground state of weakly interacting bosons that self-consistently incorporates the dynamical 3/2-body processes. [17][18][19] Using it, we found that these processes contribute to the ground state energy with the same order as the mean-field energies. Thus, the 3/2-body correlations should be incorporated self-consistently, even in the collisionless regime.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations